Pengembangan LKPD Digital Berbasis HOTS Pada Materi Dimensi Tiga - Rahma Rosaliana Saraswati; Makmuri; Ellis Salsabila (Risenologi, 2021)
This study aims to develop HOTS-based digital worksheets on three-dimensional material for grade XII high school students. This LKPD will also be equipped with a video as a stimulus in learning. This development research refers to the ADDIE model (Analyze, Design, Development, Implement, Evaluation). From the results of the research that has been described, it can be concluded that the HOTS-based digital worksheets on the three-dimensional material developed consist of 3 stages, namely introduction, content, and closing. The components in the HOTS-based digital LKPD in this three-dimensional material consist of cover pages, basic competencies, competency achievement indicators, learning objectives, apperception, basic theory, tips and tricks, sample questions, discussion of sample questions, activity instructions, problems about three dimensions, conclusions, and aphorisms related to the material. Based on the validation test of learning experts, it was found that the percentage of feasibility of learning HOTS-based digital worksheets on three-dimensional material was 70% or quite feasible. Meanwhile, for the media expert validation test, the percentage of eligibility is 95% or classified as very feasible. Based on the validation test, the percentage of the average value of 82.5% or if interpreted, the HOTS-based digital worksheet on this three-dimensional material is classified as very feasible to be used as a learning medium for teachers and students.